B-ShareAplikasi Bank Darah Untuk Mempercepat Penyediaan Informasi Darah sebagai pendukung terciptanya Smart City - mutia fadhila putri; indra maulana; andini dwi lestari; erma tita (Annual Research Seminar (ARS), 2016)
lack of information about the availability of blood to be a problem that is not uncommon in the daily life, there are many medical cases that require blood transfusion procedure. Practically, the hospital will entrust the patient’s family to find blood bags with the required blood type. Families with little knowledge about where to find blood will encounter confusing situations. Whereas they have to find it fast. if a blood transfusion is done too late, then even death may occur, because of this it is expected that the existence of a public service that can provide information quickly and accurately blood that can be utilized by the community.